Learning Design Heutagogical Approach in Developing Self-Determined Learning Skills - Ishaq; I Nyoman S. Degeng; Henry Praherdhiono; Made Duananda Kartika Degeng (Journal of Education Reseach and Evaluation, 2024)
Learning and teaching practices in various tertiary institutions (PT) remain in didactic pedagogy, perpetuating teacher-centered learning methods, thus failing to take advantage of technological developments. This research aims to develop a pedagogical approach to learning design to develop learners' self-determined learning skills through a blended learning scheme. This type of research is development research. The model used in developing the Heutagogi approach learning design is the 4D development model. The subjects of this research are learning design experts, learning media experts, and learning device experts. The subjects of this trial were all 60 students. The methods used to collect data are questionnaires and test questions. The instruments used in collecting were questionnaire sheets and test questions. Techniques for analyzing data are qualitative, quantitative, and inferential statistical descriptive analysis. The research results are as follows: First, the learning design and learning support tools for developing self-determined learning skills are valid and reliable. Secondly, there are differences in the effectiveness of learning designs for self-determined learning strategies (Heutagogi). Third, there is a correlation between the value of self-determined learning skills and course learning outcomes (CPMK). It was concluded that the Heutagogi approach learning design is suitable for use in learning and improves student learning outcomes.